2012
DOI: 10.1021/bi3000897
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella aerogenes UreF: Identification of the UreG Binding Site and Role in Enhancing the Fidelity of Urease Activation

Abstract: The Ni-containing active site of Klebsiella aerogenes urease is assembled through the concerted action of the UreD, UreE, UreF, and UreG accessory proteins. UreE functions as a metallochaperone that delivers Ni to a UreD–UreF–UreG complex bound to urease apoprotein, with UreG serving as a GTPase during enzyme activation. This study focuses on the role of UreF, previously proposed to act as a GTPase activating protein (GAP) of UreG. Sixteen conserved UreF surface residues that may play roles in protein–protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 46 publications
(172 reference statements)
5
28
0
Order By: Relevance
“…The Strep -tag II version of (UreABC) 3 :UreDFG was formed in cells transformed with pKKG containing ureDABCEFG where ureG is fused to the codons for Strep -tag II [25]. This complex was purified by use of a Strep -tactin column followed by Superdex 200 gel filtration chromatography, as previously described [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Strep -tag II version of (UreABC) 3 :UreDFG was formed in cells transformed with pKKG containing ureDABCEFG where ureG is fused to the codons for Strep -tag II [25]. This complex was purified by use of a Strep -tactin column followed by Superdex 200 gel filtration chromatography, as previously described [25].…”
Section: Methodsmentioning
confidence: 99%
“…This complex was purified by use of a Strep -tactin column followed by Superdex 200 gel filtration chromatography, as previously described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…A role as a GTPase-activating protein was suggested for UreF (41), but the UreH:UreF:UreG structure (which shows UreF binding UreG opposite the GTP site) (Fig. 2) and experimental evidence derived from mutagenesis and GTPase activity studies (42) argue against this proposal. For example, a urease activation complex containing a UreF variant exhibited enhanced GTPase activity compared with the complex with wild-type accessory protein.…”
Section: Ured/ureh: Scaffold For Recruitment Of Other Accessory Protementioning
confidence: 99%
“…Furthermore, UreABC:UreD:UreE-UreF:UreG is made in cells producing the UreE-UreF fusion protein (38). Mutagenesis studies identified Asp-80 as a key UreG residue involved in this interaction (48) and defined several residues along one face of UreF as the UreG-docking site (42). Using standard activation conditions, ϳ60% of the nascent active sites in UreABC: UreD:UreF:UreG become active (54).…”
Section: Ured/ureh: Scaffold For Recruitment Of Other Accessory Protementioning
confidence: 99%
“…8 Ka UreF alone is insoluble. 9 Ka UreG, which exists as a soluble monomer that binds one equivalent of nickel or zinc with similar affinities, 10, 11 acts as a GTPase during urease maturation, although the precise role of GTP hydrolysis in this process remains unclear. Ka UreG residues associated with a highly conserved Cys-X-His motif are hypothesized to function as the metal binding site, but substitution of one or both of these residues does not abolish metal binding.…”
mentioning
confidence: 99%